Bioefficacy of synthetic and botanical insecticides for controlling podborer (Helicoverpa armigera) and podfly (Melanagromyza obtusa) infesting vegetable purpose pigeonpea (Cajanus cajan) - PATEL, J J; PATEL, N C; JAYANI, D B; PATEL, J R; PATEL, B D (The Indian Journal of Agricultural Sciences, 2013)
A field expeliment was conducted during rainy season (kharif) 1993 and 1994 to find out an effective and economicalinsecticide for controlling podborer (Helicoverpa armigera Hubner), plume moth (Marasmarcha liophanes Mey) andpodfly (Melanagromyza obtusa Malloch) on vegetable - purpose pigeonpea [Cajanus cajan (L.) Millsp.]. Endosulfan Ec0.035% (1: 14.18) gave the highest incremental cost: benefit ratio, followed by endosulfan WP 0.035% (1 : 12.95) andchlorpyriphos 0.02%. Neem - seed - kernel suspension (NSKS) 3%, though gave 1 : 11.77 cost: benefit ratio, was lesseffective and economical for controlling these insects